The deepest kill - Black, Lisa, 1963- (Black, Lisa, 1963- Locard Institute thriller., 2024)
When the pregnant daughter of software pioneer Martin Post, the third richest man in America, is murdered, expert forensic analysts Ellie Carr and Rachael Davies, called in to investigate, are drawn into the Posts' increasingly dangerous family dynamic to determine who--and what--is at the heart of the crime.